Web-Based Administration of Online Multiple-Choice Test - Ramli, Awang (2003)
The purpose of this project is to develop a prototype of a web-based administration of online multiple-choice test system to be used in Perlis Teachers Training College, Perlis. The system was developed to facilitate in managing and administrating an online test. It is a client/server architecture which is based on intranet. Database Design Methodology and Rapid Prototyping technique were used to build the system. The system was trial-run in Perlis Teachers Training College by a group of students sitting the online test. Problems and limitations discovered were then discussed and recommendations made to overcome the limitations for the future development of the project.